1982
DOI: 10.1042/cs063045s
|View full text |Cite
|
Sign up to set email alerts
|

Raised Intracellular Sodium Consequent to Sodium-Potassium-Dependent ATPase Inhibition Does Not Cause Myogenic Contractions of 150 μm Arteries from Rat and Guinea Pig

Abstract: 1.We have examined effects of inhibition of Na+,K+-dependent ATPase in large and small arterial ring preparations from rats and guinea pigs.2. Ouabain (1 mmol/l) caused myogenic contraction of rat aorta and tail artery, but had no long-lasting effect on 150 pm mesenteric and 150 pm femoral resistance vessels over a 3 h period. Much lower concentrations of ouabain (1 pmol/l) caused contraction of guinea pig aorta, but had no effect on the mesenteric and femoral resistance vessels.3. In the mesenteric resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Mulvany et al 13 showed that, after incubation in 1 mM ouabain, the intracellular sodium increased (by approximately 50 mM at 2 hours) and there was significant depolarization of the membrane (approximately 24 mV at 3 hours); yet there was no change in resting tension at 3 hours. The difference between their investigations and ours may therefore lie in the origin of the arteries, that is, either the vascular bed or the species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mulvany et al 13 showed that, after incubation in 1 mM ouabain, the intracellular sodium increased (by approximately 50 mM at 2 hours) and there was significant depolarization of the membrane (approximately 24 mV at 3 hours); yet there was no change in resting tension at 3 hours. The difference between their investigations and ours may therefore lie in the origin of the arteries, that is, either the vascular bed or the species.…”
Section: Discussionmentioning
confidence: 99%
“…In large arteries, there is good evidence that raised intracellular sodium is associated with myogenic contraction. By use of cardiac glycosides for elevation of intracellular sodium, myogenic vasoconstriction has been shown to develop in rabbit aortic strips and rat aortic rings, 11 -12 rat and guinea pig aortic rings, 13 ' 14 and human crural and omental vessels. 1516 Similar responses have been shown by the incubation of arteries in low sodium buffer.…”
Section: S Ince the Original Observation By Tobian Andmentioning
confidence: 99%
See 1 more Smart Citation
“…'+D600" shows values obtained after 5 minutes in D600 (10 MM) In part B, the NA dose was adjusted for each vessel to give a response of about 0 3 AT] before addition of ouabain or KCl: this required about 0.2 MM NA under control and + felodipine conditions, and about 10 MM under +D600 conditions * Significantly different (P < 0.05) from control value. I Not measured (Mulvany et al, 1982a(Mulvany et al, , 1982c, ouabain exposure did not in itself produce any response. The effects of choline-substituted low-Na + solutions and of ouabain on membrane potential, E m , and on intracellular sodium concentration, [Na] u are shown in Table 2.…”
Section: Effects Of Altered Sodium Gradient On Unstimulated Vesselsmentioning
confidence: 99%
“…Some evidence in support of this mechanism has been obtained from large vessels (Reuter et al, 1973), but there is no evidence available for its presence in the smaller vessels which determine peripheral resistance. It is therefore still not certain that the pressor response to injected ouabain is due to raised [Na], (Mulvany et al, 1982a(Mulvany et al, , 1982cHermsmeyer, 1983), and at least two other mechanisms may be considered. First, ouabain can cause increased transmitter release from the vascular nerve terminals (Gillis and Quest, 1979;Aarhus et al, 1983).…”
Section: T Petersenmentioning
confidence: 99%